Online collaborative learning activities: The perspectives of minority graduate students - Kumi-Yeboah, Alex; Dogbey, James; Yuan, Guangji (Online Learning, 2017)
This exploratory study examined the perspectives of minority graduate students toward online collaborative learning activities. The participants were twenty graduate minority students (15 African Americans, five Hispanics, and five international students from Africa) in online graduate programs in instructional technology education in in the Northeastern United States. A qualitative study was conducted semi-structured interviews, focus group interviews along with observations, Data revealed that the perspectives of minority graduate students toward online collaborative learning activities could be categorized into six themes, including “(a) facilitates knowledge building and construction, (b) preference to work in small-group over whole-group activities, (c) opportunities to share and lead discussion in cross-cultural online environment (d) collaborative activities meets learning and communication styles, and (e) challenges of dealing with cultural differences, (f) lack of multicultural inclusion in the curriculum/course content. The study documents factors that facilitate cross-cultural collaborative learning activities that helped minority students to succeed in online environment.